Analisis Peramalan Penjualan pada PT. Multi Megah Mandiri untuk Tahun 2009 - Yuliany Sylvia Agustina; Haryadi Sarjono (Jurnal Riset Manajemen dan Bisnis, 2010)
PT. Mthi Megah Merdrri is a compary that runs a mantfacturebusiness. The entire manufacfuring processes oe done in the compoty. The writer also mafue.s which netlrod is the best mtong thefwe methods based an the result of the smallest etrors of the l,$E and the MAD. The'metlnds usedhere are Moving Average, Double Mwing Average, Weighted Moving overage, Expanenfi.al smoothing" ond uponantial smoothing with trerrd. This resesch uses descrptive meihod. The obiective is to study the sales of PT Mutti Mega lfierdiri in details to get valid dota to predict the sales performance af the comp*ty for the following yem. this reseoch uses primry dda, which oe collected directly from reliable resources. The analysis indicates that tte best method based om the MAD ond the MSE is the upanential smoothing fucause theforecasting erroris the smallest among the 5 methods. It is recommended that the company use the method to forecast its sales performance in thefollowing yew becanse of its evident accuracy.KAwords : Forecasting, Sales, IvIAD, MSE, Eqtonential smoothing